Positive Character and Academic Achievement: The Moderating Role of Family Function - Hasanuddin Hasanuddin; Rahmi Lubis; Lince Kristina Tafonao; Zain Adawiyah (Applied Quantitative Analysis, 2024)
Student academic achievement is an indicator of success in studying in college. Student habits in carrying out tasks reflected in personal character will impact student learning achievement. However, the positive character does not always influence learning achievement. Other factors that can weaken the role of positive character in academic achievement include family function. This research examines the moderating role of family function in determining the strength of the influence of positive character on student academic achievement. The 201 students majoring in natural sciences selected using stratified random sampling were involved in this explanatory quantitative research. Researchers employed the family function, the noble character scales, and the student cumulative achievement index. Data analysis used the Jamovi statistical software moderation test version 2.0.0. The results show that family function determines the magnitude of the influence of positive character on academic achievement. For students with high family function, character determines significantly academic achievement. On the contrary, for students with low family function. The study is beneficial for educational counsellors in overcoming the problem of low academic achievement by focusing on developing character and improving family function.